Thank you for arguing : what Aristotle, Lincoln, and Homer Simpson can teach us about the art of persuasion - Heinrichs, Jay. (New York : Three Rivers Press, 2013)
Thank You for Arguing is your master class in the art of persuasion, taught by professors ranging from Bart Simpson to Winston Churchill. The time-tested secrets this book discloses include Ciceros three-step strategy for moving an audience to actionas well as Honest Abes Shameless Trick of lowering an audiences expectations by pretending to be unpolished. But its also replete with contemporary techniques such as politicians use of code language to appeal to specific groups and an eye-opening assortment of popular-culture dodgesincluding The Yoda Technique, The Belushi Paradigm, and The Eddie Haskell Ploy. Whether youre an inveterate lover of language books or just want to win a lot more anger-free arguments on the page, at the podium, or over a beer, Thank You for Arguing is for you. Written by one of todays most popular language mavens, its warm, witty, erudite, and truly enlightening. It not only teaches you how to recognize a paralipsis and a chiasmus when you hear them, but also how to wield such handy and persuasive weapons the next time you really, really want to get your own way.
Introduction : Open your eyes: the invisible argument -- Offense : Set your goals: Cicero?'s lightbulb -- Control the tense: Orphan Annie?'s law -- Soften them up: character, logic, emotion -- Get them to like you: Eminem?'s rules of decorum -- Make them listen: the Lincoln gambit -- Use your craft: the Belushi paradigm -- Show you care: Quintilian?'s useful doubt -- Control the mood: the Aquinas maneuver -- Turn the volume down: the scientist?'s lie -- Gain the high ground: Aristotle?'s favorite topic -- Persuade on your terms: what "is" is -- Control the argument: Homer Simpson?'s canons of logic -- Defense : Spot fallacies: the seven deadly logical sins -- Call of foul: Nixon?'s trick -- Know whom to trust: persuasion detectors -- Find the sweet spot: more persuasion detectors -- Advanced offense : Get instant cleverness: Monty Python's treasury of wit -- Speak your audience?'s language: the rhetorical ape -- Make them identify with your choice: the mother-in-law ruse -- Lead your tribe: Mandela's halo -- Avoid apologizing: Apple's fall -- Seize the occasion: Stalin's timing secret -- Use the right medium: the jumbotron blunder -- Advanced agreement : Give a persuasive talk: the oldest invention -- Capture your audience: the Obama identity -- Use the right tools: the Brad Pitt factor -- Run an agreeable country: rhetoric?'s revival -- Appendices : Argument lab ; The tools ; Glossary ; Chronology.
Includes index.
Includes bibliographical references (pages 395-396) and index.
Keywords: Persuasion (Rhetoric); Debates and debating